Electrochemical Performance and Stability of Ba?.?Sr?.?Co?.?Fe?.?O??? for Oxygen Transport Membranes - Niedrig, Christian (Schriften des Instituts für Angewandte Materialien - Werkstoffe der Elektrotechnik, Karlsruher Institut für Technologie / Institut für Angewandte Materialien - Werkstoffe der Elektrotechnik, 2015)
Mixed ionic-electronic conducting (MIEC) ceramics as oxygen transport membranes (OTMs) can provide high oxygen permeation rates at comparably low energy demands. For this purpose, Ba?.?Sr?.?Co?.?Fe?.?O??? (BSCF) shows the best performance under ideal operating conditions. Thermal and chemical stability investigations, electrical behavior ?(T,pO?,t), and oxygen exchange parameter extraction by means of electrical conductivity relaxation resulted in a far better understanding of the BSCF system.